2021
DOI: 10.1002/ajcp.12498
|View full text |Cite
|
Sign up to set email alerts
|

Development of a support for Black Lives Matter measure among racially–ethnically diverse college students

Abstract: This paper developed and validated a new measure of support for the Black Lives Matter (BLM) movement among a racially–ethnically diverse sample of college students. The measure focuses on the movement’s principles of Black liberation, intersectionality, and alliance building. Participants included 1934 college students (75% female) from a large public Southwestern university. The factor structure was supported by exploratory and confirmatory factor analyses, resulting in an 18‐item measure, Support for Black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Responses were measured on a 5-point Likert-type scale (1 = Strongly Oppose to 5 = Strongly Support ). Internal reliability estimates in the original validation study were .94 for BLM-Black Liberation and .92 for BLM-Diversity Values among racial minority college students, including Asian Americans (Yoo et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses were measured on a 5-point Likert-type scale (1 = Strongly Oppose to 5 = Strongly Support ). Internal reliability estimates in the original validation study were .94 for BLM-Black Liberation and .92 for BLM-Diversity Values among racial minority college students, including Asian Americans (Yoo et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The Support for BLM Measure-Short (Yoo et al, 2021) is a 12-item measure including two subscales that assess support for goals of the BLM movement: BLM-Black Liberation and BLM-Diversity Values . BLM-Black Liberation (6 items) measured support for BLM because the movement raises awareness and challenges the structural inequality and racism experienced by Black individuals (e.g., “The Black Lives Matter movement argues there is a disproportionate impact of state and police violence on Black lives”).…”
Section: Methodsmentioning
confidence: 99%
“…ANES unfortunately does not offer a “queer” option for a sexual identity marker, even though queer identified individuals seem to challenge racial identities more than people who accept the lesbian or gay classifications (Goldberg et al, 2020 ; Worthen, 2020 ). The use of a scale that captures the approval of the intersectional goals of BLM might alter perceptions of BLM among sexual minorities (Yoo et al, 2021 ). Finally, a study of intersecting racial-sexual identities could be informative because LGB and heterosexual people of color might have different relationships to the Black community than White people of their same sexual identity (Battle & Harris, 2013 ; Sarno, et al, 2015 ; VanDaalen & Santos, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that Black and Latinx Americans identified as lesbian, gay, or bisexual at slightly higher rates than white individuals (Bridges & Moore, 2018 ; Herek et al, 2010 ) and Black and Latinx queer people protested racism more often than Black and Latinx heterosexuals (Battle & Harris, 2013 ; Terriquez, 2015 ). White individuals generally preferred traditional racial rules and expressed more reservations over BLM (Hamel et al, 2020 ; Yoo et al, 2021 ), while Black people generally joined more BLM protests than whites (Arora & Stout, 2019 ; Holt & Sweitzer, 2018 ; Intravia et al, 2018 ; Riley & Peterson, 2020 ). Other studies suggested that Latinx and Asian-American sentiments were somewhere between the Black/White divide (Corral, 2020 ; Kilgo & Mourão, 2019 ; Yellow Horse et al, 2021 ) and that the increased percentage of racial minorities among LGB populations might produce greater LGB support of BLM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation